A Role for Ubiquitination in Mitochondrial Inheritance in Saccharomyces cerevisiae - Fisk, Harold A. (The Rockefeller University Press, 1999)

(untitled)
The smm1 mutation suppresses defects in mitochondrial distribution and morphology caused by the mdm1-252 mutation in the yeast Saccharomyces cerevisiae. Cells harboring only the smm1 mutation themselves display temperature-sensitive growth and aberrant mitochondrial inheritance and morphology at the nonpermissive temperature. smm1 maps to RSP5, a gene encoding an essential ubiquitin-protein ligase. The smm1 defects are suppressed by overexpression of wild-type ubiquitin but not by overexpression of mutant ubiquitin in which lysine-63 is replaced by arginine. Furthermore, overexpression of this mutant ubiquitin perturbs mitochondrial distribution and morphology in wild-type cells. Site-directed mutagenesis revealed that the ubiquitin ligase activity of Rsp5p is essential for its function in mitochondrial inheritance. A second mutation, smm2, which also suppressed mdm1-252 defects, but did not cause aberrant mitochondrial distribution and morphology, mapped to BUL1, encoding a protein interacting with Rsp5p. These results indicate that protein ubiquitination mediated by Rsp5p plays an essential role in mitochondrial inheritance, and reveal a novel function for protein ubiquitination.